In ricordo Di P. Gianpaolo Salvini S.I. (1936-2021) - La Civiltà Cattolica; Salvini, Gianpaolo 1936-2021 (2021)
GianPaolo Salvini, was the editor of La Civiltà Cattolica for 26 years and an active writer emeritus until the end. We retrace his long and intense journey from his youth in Milan to his priestly and cultural formation during the years of the Vatican II Council, to his commitment as editor of the magazine Aggiornamenti Sociali and then, from 1984, as editor of our magazine. An expert in economics and demography, in his long career as a writer Fr Salvini dealt with a wide range of topics in the light of the Church’s social teaching.
Keywords: Nachruf